2019
DOI: 10.1016/j.omtn.2019.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0016070 Is Associated with Pulmonary Arterial Hypertension by Promoting PASMC Proliferation

Abstract: Noncoding RNAs play an important role in the pathogenesis of pulmonary arterial hypertension (PAH). In this study, we investigated the roles of hsa_circ_0016070, miR-942, and CCND1 in PAH. circRNA microarray was used to search circRNAs involved in PAH, whereas real-time PCR and western blot analysis were performed to detect miR-942 and CCND1 expression in different groups. In addition, the effect of miR-942 on CCND1 expression, as well as the effect of hsa_circ_0016070 on the expression of miR-942 and CCND1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 43 publications
1
59
0
Order By: Relevance
“…Zhou et al (9) have demonstrated that circRNA HEcT domain-containing E3 ubiquitin protein ligase 1 (HEcTd1) mediates silica-induced macrophage activation by regulating the circHEcTd1/HEcTd1 axis and zinc finger cccH-type containing 12A-dependent ubiquitination process. Zhou et al (10) have reported that circular RNA hsa_circ_0016070 is associated with pulmonary arterial hypertension. In addition, circRNA antisense non-coding RNA in the INK4 locus and circRNA checkpoint with forkhead and ring finger domains (circcHFR) have been confirmed to modulate the progression of atherosclerosis (11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al (9) have demonstrated that circRNA HEcT domain-containing E3 ubiquitin protein ligase 1 (HEcTd1) mediates silica-induced macrophage activation by regulating the circHEcTd1/HEcTd1 axis and zinc finger cccH-type containing 12A-dependent ubiquitination process. Zhou et al (10) have reported that circular RNA hsa_circ_0016070 is associated with pulmonary arterial hypertension. In addition, circRNA antisense non-coding RNA in the INK4 locus and circRNA checkpoint with forkhead and ring finger domains (circcHFR) have been confirmed to modulate the progression of atherosclerosis (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…circular RNAs (circRNAs) are a type of single-stranded RNAs with a covalently closed continuous loop that are produced by backsplicing (6) and are resistant to exonuclease-mediated degradation (7). Numerous studies have demonstrated that circRNAs are associated with cardiac repair (8), silica-induced macrophage activation (9), pulmonary arterial hypertension (10) and atherosclerosis (11). Microarray analysis has revealed that circ_0010283 is upregulated in oxidized low-density lipoprotein (ox-LdL)-induced VSMcs (12).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Circ_0078767 signi cantly repressed the proliferation of NSCLC cells [17]. CircRNA hsa_circ_0016070 was reported to promote the proliferation of pulmonary artery smooth muscle cells [15]. CircARHGAP10 suppresses NSCLC progression by promoting GLUT1 expression via sponging miR-150-5p [18].…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) is an endogenous non-coding RNA, forms a closed continuous loop by back splicing with covalently joined between 3' and 5' ends [10]. Accumulating researchers reveal the critical role of circRNAs in multiple biological processes [11] and diseases [12,13], including cancer and COPD [14][15][16]. The anomalously expressed circRNAs might provide new diagnose biomarker and therapeutic targets in diseases.…”
Section: Introductionmentioning
confidence: 99%
“…11 Due to the circular structure, circRNAs are highly conserved and stable than linear mRNAs. 12 CircRNAs are mainly located in the cytoplasm, 13 and most of the circRNAs are generated from one or more coding exons via a backsplice mechanism. 11 CircRNAs could promote gene transcription, and function as modifiers of parental gene expression.…”
Section: Introductionmentioning
confidence: 99%